Competency-structured case discussion in the morning meeting: enhancing CanMEDS integration in daily practice - Hassan IS; Kuriry H; Al Ansari L; Al-Khathami A; Al Qahtani M; Al Anazi T; Farooqui M; AL-Jahdali H (Advances in Medical Education and Practice, 2015)
Imad Salah Hassan, Hadi Kuriry, Lina Al Ansari, Ali Al-Khathami, Mohammed Al Qahtani, Thari Al Anazi, Mahfooz Farooqui, Hamdan Al Jahdali Department of Medicine 1443, King Saud bin Abdulaziz University for Health Sciences, King Abdulaziz Medical City, Riyadh, Kingdom of Saudi Arabia Abstract: Outcome-focused, competency-based educational curricula have become the norm in residency training programs. The Canadian Medical Education Directives for Specialists (CanMEDS) framework is one example of such a curriculum. However, models for incorporating all the competencies in everyday clinical practice have been difficult to accomplish. In this manuscript, a CanMEDS, competency-structured, acute case discussion in a regular morning meeting was undertaken. All the diagnostic and therapeutic interventions were explicitly organized and discussed under their respective CanMEDS competency headings. Post exercise, the majority of residents felt that they were more competent in all the competencies and indicated their willingness to continue having similarly structured acute case discussions in the future. Keywords: CanMEDS roles, residents, morning meeting